Assessment of novel strategies for the prevention and treatment of feline upper respiratory tract infections in shelters and feline herpesvirus-1 in laboratory settings - Contreras, Elena T., author; Lappin, Michael R., advisor; Olea-Popelka, Francisco J., committee member; Dow, Steven W., committee member; Mayo, Christie E., committee member; Veir, Julia K., committee member (Colorado State University. Libraries, 2019)
Feline upper respiratory tract infection (URI) and its pathogens are ubiquitous in the feline population. Most URI cases are due to viral infections with feline herpesvirus-1 (FHV-1) and/or feline calicivirus (FCV) with secondary bacterial infections. After acute exposure to FHV-1, most cats develop persistent, latent infections with reactivation particularly during times of stress and immune suppression. Clinical signs including ocular and nasal discharge, sneezing, conjunctivitis, anorexia, lethargy, and pyrexia can vary in severity from mild and transient to severe and life-threatening. Preventive measures such as vaccination, stress reduction, environmental modifications, and infection control have lessened illness, recurrence, and spread, and many successful therapies such as antibiotics for secondary bacterial components, systemic and ocular antivirals for FHV-1, supportive care, and non-specific immune stimulation have helped to reduce the severity of illness and decrease mortality in cats. Despite these advancements in management strategies, many cats and kittens continue to suffer from URI, and those in crowded environments continue to become severely ill and either die or are euthanized. Furthermore, many animal shelters still lack information and resources regarding successful implementation of URI prevention and treatment protocols, and thus URI remains one of the most common medical reasons for euthanasia in shelters. This syndrome results in poor quality of life, and extended lengths of stay in shelters can lead to high financial burdens. Further work is needed to better understand the pathogenesis of the syndrome as well as improved preventives and treatments. The goals of the work described in this dissertation were to evaluate novel preventive and treatment strategies to decrease the incidence and severity of URI in shelters and with an emphasis on FHV-1 in experimental studies. This body of work was conducted in both the controlled research environment as well as in the animal shelter environment. Chapter 1 provides an overview of URI with a specific focus on FHV-1 and FCV and Chapter 2 presents the brief research objectives for each of the studies in this body of work. Three of the studies (Chapters 4, 5, and 7) in this body of work evaluated novel immune stimulants and preventive measures for primary FHV-1 infection and recrudescent FHV-1 in purpose-bred, experimentally infected cats in a controlled research setting. Chapter 4 evaluated a plant-based nutraceutical, Carnivora™, with anti-inflammatory and immune modulating components and its effects on recrudescence of clinical signs and viral shedding in young adult cats upon repeat challenge of FHV-1. Our study found that cats that were administered Carnivora™ had significantly less clinical manifestations of FHV-1 disease when compared to the control group. Chapter 5 assessed a new mucosal formulation of a liposomal toll-like receptor immune stimulant (LTC) as both a preventive and treatment for FHV-1 in purpose-bred kittens. This study found that administration of LTC as a preventive 24 hours prior to FHV-1 challenge resulted in some positive clinical effects and decreased shedding of FHV-1 DNA, whereas administration of LTC as a treatment during illness with FHV-1 did not influence clinical course of FHV-1 illness. Chapter 7 explored the use of a pheromone product in these same purpose-bred kittens and its effects on stress reduction, relaxation, and recrudescence of FHV-1 clinical signs. Results indicated that the pheromone product decreased stress, increased relaxation, and decreased some of the clinical signs of FHV-1 recrudescence in the kittens. Two of the studies (Chapters 3 and 6) evaluated novel immune stimulants and preventives in open-admission shelter environments. Chapter 3 explored whether the addition of an inactivated, broader spectrum FCV vaccine to a standard vaccination protocol at a shelter, would result in decreased incidence, duration, and severity of URI and oral ulceration in cats. The study did not find evidence that the additional vaccine protected cats from developing URI, severe URI, or oral ulceration indicative of calicivirus. Chapter 6 evaluated administration of the LTC discussed in Chapter 5 to cats in an open-admission shelter. Cats were administered the LTC upon admission to determine whether it would result in decreased incidence and severity of URI. The study did not find significant evidence that the LTC protected cats from developing URI or severe URI in the shelter, nor did it significantly impact clinical course of illness. Although neither of the shelter experiments had significant findings regarding the preventive product being tested, results provided additional important information regarding immune compromise and potential for immunomodulatory therapeutics and stimulation in the shelter environment, risk factors contributing to URI onset, timing, prevalence, severity, and outcomes in shelter environments. The work described in this dissertation has increased our knowledge of FHV-1 preventive and treatment options and mitigating and risk factors that might contribute to URI occurrence, recrudescence, and resolution. We hope that the findings in this work will help to decrease prevalence and severity of URI and improve the outcome for cats and kittens with URI, especially in the shelter environment.
Keywords: cat; FHV-1; pheromone; FCV; calicivirus; FURI